Dampak Ukuran Perusahaan, Profitability sareng Likuiditas CSRD Indeks Syariah Sektor Perdagangan, Jasa sareng Investasi - Sofyan Halim; Fatimah Sinar Mustika (Neolectura, 2022)
Obtaining knowledge and proof of research that examines the relationship between SCR Disclosure variables from CSR disclosures influenced by company size, profitability and liquidity in issuers of the Indonesian Sharia Stock Index of the trading, services and investment sectors is the purpose of the research. The Research use quantitative causal research methods, with samples using the Slovin formula. Research results that CSR disclosures are positively significantly influenced by the Size and Capacity of the Company, Earnings Per Share which is part of the profitability ratio negatively affected the disclosure of CSR programs, and CSR Program Disclosure is not significantly affected by the Liquidity factor either tested with Current Ratio or with Quick Ratio, but through testing with the simultaneous of F Test all The Variables Independents studied significantly affect CSR disclosures on the Issuer of shares of Indonesian Sharia Index of Trade, Services and Investment Sectors